Phase III Randomized Study of Ribociclib and Fulvestrant in Hormone Receptor-Positive, Human Epidermal Growth Factor Receptor 2-Negative Advanced Breast Cancer: MONALEESA-3 - Slamon, Dennis J; Neven, Patrick; Chia, Stephen; Fasching, Peter A; De Laurentiis, Michelino; Im, Seock-Ah; Petrakova, Katarina; Bianchi, Giulia Val; Esteva, Francisco J; Martín, Miguel; Nusch, Arnd; Sonke, Gabe S; et al. (Journal of clinical oncology, 2018)
Purpose This phase III study evaluated ribociclib plus fulvestrant in patients with hormone receptor-positive/human epidermal growth factor receptor 2-negative advanced breast cancer who were treatment naïve or had received up to one line of prior endocrine therapy in the advanced setting. Patients and Methods Patients were randomly assigned at a two-to-one ratio to ribociclib plus fulvestrant or placebo plus fulvestrant. The primary end point was locally assessed progression-free survival. Secondary end points included overall survival, overall response rate, and safety. Results A total of 484 postmenopausal women were randomly assigned to ribociclib plus fulvestrant, and 242 were assigned to placebo plus fulvestrant. Median progression-free survival was significantly improved with ribociclib plus fulvestrant versus placebo plus fulvestrant: 20.5 months (95% CI, 18.5 to 23.5 months) versus 12.8 months (95% CI, 10.9 to 16.3 months), respectively (hazard ratio, 0.593; 95% CI, 0.480 to 0.732; P < .001). Consistent treatment effects were observed in patients who were treatment naïve in the advanced setting (hazard ratio, 0.577; 95% CI, 0.415 to 0.802), as well as in patients who had received up to one line of prior endocrine therapy for advanced disease (hazard ratio, 0.565; 95% CI, 0.428 to 0.744). Among patients with measurable disease, the overall response rate was 40.9% for the ribociclib plus fulvestrant arm and 28.7% for placebo plus fulvestrant. Grade 3 adverse events reported in ≥ 10% of patients in either arm (ribociclib plus fulvestrant v placebo plus fulvestrant) were neutropenia (46.6% v 0%) and leukopenia (13.5% v 0%); the only grade 4 event reported in ≥ 5% of patients was neutropenia (6.8% v 0%). Conclusion Ribociclib plus fulvestrant might represent a new first- or second-line treatment option in hormone receptor-positive/human epidermal growth factor receptor 2-negative advanced breast cancer.